Factores que contribuyen a la variación de la productividad del maíz entre fincas en el sector de Quinsaloma - La Ercilia. - Tigrero Zapata, Gabriela Jamilex (2017)
The wide variation in yield between farms has the capacity to reduce the volume of production, in this case in the maize area of La Ercilia - Quinsaloma. The objective of this research was to identify and describe the agro-socio-economic factors that could be contributing to this variation. Through the application of a survey to a group of 62 producers carried out in the August-September 2017 period, information relevant to the proposed objective was obtained. The survey consisted of two sets of questions, each battery with the number needed to identify the factors of agronomic nature first, and socio-economic later. The study revealed a rich experience in the agronomic management of the crop and the wisdom of the farmers in selecting the hybrid seed with the best chance of success. They know how to deal with sanitary and weed problems quite well, although there is room to improve the efficiency of use of agrochemicals and reduce the risk of environmental contamination. Early sowing at the beginning of the rainy season is widely known and applied as a good crop practice because of its confirmed influence on maize productivity. In general there is generosity in the use of mineral fertilization although surprisingly no one performs soil analysis and the benefits of relying on their results for the rational use of fertilizers are ignored. In the socio-economic field, the investigation revealed that a significant proportion of the sample of producers leases or lends land to plant corn, mostly in small areas. It also revealed characteristics of age and schooling that could have an influence against the constant modernization of the crop to distance the income from the total costs. The action of spending own resources combined with family support to bring the crop, reflect the importance of the role of corn in the culture of the area and economy of families engaged in this activity. In summary, while decisions and the management of fertilization and soil quality, stands out as the factor with wide potential to influence the variability of maize yield in the agronomic dimension, in the socio-economic field it is difficult to arrive at a conclusion, although the possession of land with corn could be in the front in terms of the level of influence exercised. Management of fertilization and land tenure can sustain future lines of research on the subject. Keywords: Production, agro-environmental, socio-economic, rainy period.